2023
DOI: 10.1039/d3fo00354j
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of DSS-induced colitis in mice with water kefir microbiotaviaanti-inflammatory and microbiota-balancing activity

Abstract: Water kefir, a natural and stable functional microbiota system consisting of a symbiotic mixture of probiotics, showed multiple bioactivities, but it was little known about the effect of water kefir...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In particular, mandelonitrile, alpha-terpineol, and linalool have been documented for their anti-inflammatory effects. Remarkably, alpha-terpineol demonstrated efficacy in alleviating UC. ,, The molecular docking assay was further employed to score PSEO and potential target proteins with respect to UC for preliminary validation of network pharmacology predictions. Moreover, Western blotting and immunofluorescence assays were conducted for experimental validation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, mandelonitrile, alpha-terpineol, and linalool have been documented for their anti-inflammatory effects. Remarkably, alpha-terpineol demonstrated efficacy in alleviating UC. ,, The molecular docking assay was further employed to score PSEO and potential target proteins with respect to UC for preliminary validation of network pharmacology predictions. Moreover, Western blotting and immunofluorescence assays were conducted for experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the goblet cell numbers and These investigations have demonstrated that the pathological manifestations of the spleen offer valuable insights into the body's splenic immune function, serving as a more objective measure of immunocompetence. 32,33 Furthermore, spleen hematoxylin−eosin staining exhibited that there was a lot of bleeding in the DSS group, poorly defined red marrow and white marrow, and infiltration of inflammatory cells and even structural breakage, whereas PSEO treatment attenuated these conditions (Figure 4F). SEM images revealed that DSS-induced UC mice displayed drastic alterations of ultramorphology as evidenced by the rough surface and incomplete form, suggesting that PSEO might be protective against UC through improving intestinal barrier functions (Figure 4G).…”
Section: Phytochemical Compositionmentioning
confidence: 98%